Decoding Turkey's institutional accommodation in the changing international order: the UN and G20 cases - KURŞUN, ALİ MURAT; PARLAR DAL, EMEL; MEHMETCİK, HAKAN (PALGRAVE MACMILLAN LTD, 2019)
This article attempts to assess Turkey's accommodation to the US-led global governance at the institutional level using T.V. Paul's institutional accommodation strategy. In doing so, it specifically deals with Turkey's accommodation in two specific international institutions: the UN as the major global governance institution and the G20 as an informal international platform. Departing from the existing literature on accommodation, this study first proposes and outlines a new typology for peaceful accommodation. The second part seeks to analyze and compare the main driving factors of Turkey's institutional accommodation in the UN and G20. Finally, the third part seeks to operationalize the analytical framework of institutional accommodation strategy for understanding Turkey's institutional accommodation in the examples of the UN and G20. This study concludes that although Turkey's accommodation and its institutional form can be nuanced from that of other rising states, Turkey has the capacity to act as an intermediary accommodator for becoming a responsible stakeholder in global governance.
Keywords: Turkey in global governance; Accommodation; International order; United Nations; G20; REGIONAL POWER; CIVILIZATIONS; ALLIANCE; SOCIETY; CHINA